85.1k views
0 votes
Use the Function f(x)=6x-1 Which equation correctly describes f(b)?

a.) f(b)=6b-1
b.)= f(b)=6bx-1
c.)f(x)=6b-1
d.) b=6x-1

User Shar
by
4.7k points

2 Answers

2 votes

f(x) and f(b) are very similar. The only difference is that in every place where x is in the function, we now will plug in b. This is just like plugging in a number. For example, if our function was f(x) and we had to plug in 4, it might look something like this: f(4). Very similar, and we know how to plug that number in.

Let's do the same thing with b.

f(x) = 6x - 1

f(b) = 6b - 1

Hope this helps!! :)

User Rmeakins
by
5.1k points
5 votes

Answer:

a

Explanation:

To obtain f(b) substitute x = b into f(x) , that is

f(b) = 6(b) - 1 = 6b - 1

User Johanvs
by
4.5k points